Uric acid and left ventricular hypertrophy: another relationship in hemodialysis patients - Selim, G; Stojceva-Taneva, O; Tozija, L; Zafirova Ivanovska, Beti; Spasovski, G; Gerasimovska, V; Petronijevic, Z; Trajcheska, Lada; Dzekova-Vidimliski, P; Gjorgjievski, N; Pavleska-Kuzmanovska, S; Kabova, A; et al. (Oxford Academic, 2019)
Background The impact of serum uric acid (UA) on morbidity and mortality in hemodialysis (HD) patients is quite controversial in relation to the general population. The aim of this study was to evaluate the association of serum UA with both mortality and left ventricular hypertrophy (LVH) in HD patients. Methods This longitudinal study enrolled 225 prevalent HD patients who were classified into three groups according to their follow-up-averaged UA (FA-UA) levels: low FA-UA (FA-UA <400 µmol/L), intermediate/reference FA-UA (FA-UA between 400 and 450 µmol/L) and high FA-UA (FA-UA >450 µmol/L). Echocardiography was performed on a nondialysis day and the presence of LVH was defined based on a left ventricular mass index (LVMI) >131 and >100 g/m2 for men and women, respectively. The patients were followed during a 60-month period. Results The mean FA-UA level was 425 ± 59 µmol/L (range 294–620). There was a consistent association of higher FA-UA with better nutritional status (higher body mass index, normalized protein catabolic rate, creatinine, albumin and phosphorus), higher hemoglobin, but lower C-reactive protein and LVMI. During the 5-year follow-up, 81 patients died (36%) and the main causes of death were cardiovascular (CV) related (70%). When compared with the reference group, the hazard ratio for all-cause mortality was 1.75 [95% confidence interval (CI) 1.02–2.98; P = 0.041] in the low FA-UA group, but there was no significant association with the high FA-UA group. In contrast, FA-UA did not show an association with CV mortality neither with the lower nor with the high FA-UA group. The unadjusted odds ratio (OR) of LVH risk in the low FA-UA compared with the reference FA-UA group was 3.11 (95% CI 1.38–7.05; P = 0.006), and after adjustment for age, gender, diabetes and CV disease, ORs for LVH persisted significantly only in the low FA-UA group [OR 2.82 (95% CI 1.16–6.88,); P = 0.002]. Conclusions Low serum UA is a mortality risk factor and is associated with LVH in HD patients. These results are in contrast with the association of UA in the general population and should be the subject of further research.
Keywords: chronic hemodialysis; left ventricular hypertrophy; mortality; uric acid